2016
DOI: 10.1189/jlb.2hi1115-525r
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell expression of ADAM23 governs T cell proliferation and cytokine production through the α(v)β(3) integrin receptor

Abstract: ADAM23 is a member of the brain macrophage-derived chemokine family. Structural homology of ADAM proteins suggests their function as integrin receptors. Previous studies have linked ADAM23 as a dominant contributor to brain development and cancer metastasis. The present studies now show that ADAM23 expression on DCs partially governs antigen-presentation capacities to responder CD4 T cells. With the use of RNAi approaches, knockdown of ADAM23 in murine BMDCs resulted in impaired T cell activation, proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…Thus, This effect might not only occur in breast cancer but also could be a general feature of cells with dysregulated cell cycle. Secondly, metalloprotease and adhesion molecules, MMP9 and ADAM23, are involved in the breakdown of the extracellular matrix in physiological processes such as embryonic development, reproduction, and tissue remodeling [40]; they also play an important role in metastasis of cancer [41]. Studies have shown that a loss of expression of ADAM23 gene and its correlation with promoter methylation has been frequently reported in breast cancer, brain cancer, and pancreatic cancer [42,43].…”
Section: Adk-l Affects the Expression Of Genes Linked To Cancer Cell mentioning
confidence: 99%
“…Thus, This effect might not only occur in breast cancer but also could be a general feature of cells with dysregulated cell cycle. Secondly, metalloprotease and adhesion molecules, MMP9 and ADAM23, are involved in the breakdown of the extracellular matrix in physiological processes such as embryonic development, reproduction, and tissue remodeling [40]; they also play an important role in metastasis of cancer [41]. Studies have shown that a loss of expression of ADAM23 gene and its correlation with promoter methylation has been frequently reported in breast cancer, brain cancer, and pancreatic cancer [42,43].…”
Section: Adk-l Affects the Expression Of Genes Linked To Cancer Cell mentioning
confidence: 99%
“…With the possibility that Gal-8 may stimulate APC to sustain T cell activation after priming, we investigated whether this lectin displayed a direct effect on DC function. BMDCs, differentiated in vitro from GM-CSF/IL-4 conditioned mice bone marrow cultures, constitute a DC model that has been largely used to study many aspects of APCs [19][20][21][22][23]. Recently, it has been demonstrated that CD11c + BMDC cultures comprise a heterogeneous population of DCs (GM-DC) and macrophages (GM-M) [24].…”
Section: Gal-8 Induces DC Activationmentioning
confidence: 99%
“…AIF1 was knocked down using an ECM 830 (BTX, Holliston MA) square wave electroporator with 1 nanomole (nmol) of siRNA oligos in 4 mm gap cuvettes in 200 μl of Opti-MEM (Thermo Fisher Scientific) with the following settings: 310 V, 10 ms, 1 pulse. AIF1 siRNA (siAIF1) sequence used: ‘5-GGCAAGAGAUCUGCCAUCUUG-3’ (Thermo Fisher Scientific, Grand Island NY), as previously described [18, 20]. Scrambled siRNA served as controls (siControl): ‘5-GGGCTCTACGCAGGCATTTAA-3’.…”
Section: Methodsmentioning
confidence: 99%
“…siAIF1 or siControl DC expanded OT-I CD8 + T cells were collected, washed, and plated with target CFSE labeled-CD4 + T cells isolated from WT mice using negative depletion approaches, as previously described [18, 20]. Briefly, the WT CD4 + T cells were split into two equal groups: SIINFEKL peptide-pulsed and scrambled control peptide-pulsed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation